Il terzo sesso a teatro: Il "femminiello" napoletano e l’estetica del "camouflage" - Beato, Massimo Roberto (Mimesis Journal, 2024)
The rise of a different gender incorporating the feminine and the masculine is a phenomenon occurring in many cultures and in nearly all historical ages, but it assumes unique features in Naples. In fact, the culture of the femminiello is deeply rooted in Neapolitan tradition. It is a tricky figure to categorize as it embeds different forms of sexuality, thus remaining highly distinctive and intimately entwined with the tradition. The essay attempts to illustrate how Neapolitan dramaturgy has treated this remarkable queer figure. It also aims to point out how, in the plays examined, the character of the femminiello has exerted a crucial function in the rising debate on gender minorities, becoming somehow the (Neapolitan) ambassador of the struggle for the emancipation of subjects “outside the sexual norm”.